(untitled) (The Science Post, 2025)
Effective thermal management is critical for ensuring the safety, performance, and longevity of high-performance electric vehicle (EV) batteries. This study presents the design, simulation, optimization, and experimental validation of a phase change material (PCM)-based thermal management system (TMS) for lithium-ion battery modules. Various PCM candidates, including composite materials enhanced with thermally conductive additives, are evaluated to improve heat dissipation and mitigate localized hotspots. A three-dimensional thermal model of the battery pack is developed using computational tools, incorporating heat generation, conduction, convection, and phase change phenomena. Multi-objective optimization is applied to determine optimal PCM thickness, melting temperature, and thermal conductivity to achieve uniform temperature distribution and minimize thermal stress. A small-scale prototype of the optimized system is fabricated and tested under controlled charge-discharge cycles. Experimental results validate the simulation findings, demonstrating that the PCM-based TMS effectively reduces peak temperatures, improves thermal uniformity, and enhances overall battery performance. The proposed methodology provides a practical approach for integrating advanced thermal management solutions in EV battery systems.